Automatic thoughts, cognitive distortions, dysfunctional attitudes, core beliefs, and ruminative response styles in unipolar major depressive disorder and bipolar disorder: a comparative study. Issue 4 (2nd October 2019) - Yesilyaprak, Nurgul; Batmaz, Sedat; Yildiz, Mesut; Songur, Emrah; Akpinar Aslan, Esma
ABSTRACT: OBJECTIVES: We aimed to compare patients with bipolar disorder and major depressive disorder, who were either in an acute depressive episode or in remission, and a healthy control group on their cognitions related to depression and mania/hypomania, and on their response styles. METHODS: A total of 300 participants who presented to our outpatient psychiatry department were included in the study (100 participants with unipolar depression (DG), 100 with bipolar disorder, and 100 with no previous or current psychiatric disorder (CG)). The participants completed the Cognition Checklist (CCL), the Cognition Checklist for Mania (CCL-M-R), the Cognitive Distortions Questionnaire (CDQ), the Dysfunctional Attitude Scale (DAS), the Hypomanic Attitudes and Positive Predictions Inventory (HAPPI), the Brief Core Schemas Scale (BCSS), Ruminative Response Scale (RRS), and the Responses to Positive Affect Questionnaire (RPAQ). The groups were compared with each other by one-way analysis of variance, independent samples t-test, and chi-square tests. RESULTS: The DG scored higher than the other groups on the CCL, the frequency and intensity subscales of the CDQ, the DAS, and the negative-self and negative-others subscales of the BCSS, the RRS, and on the dampening subscale of the RPAQ. The clinical groups scored higher than the CG on the scores of the relationships subscale of the CCL-M-R, the total score of the CDQ, and the HAPPI. The CG scored higher than the clinical groups on the positive-self subscale of the BCSS, and on the emotion focused positive rumination subscale. CONCLUSIONS: These findings are important in the differential diagnosis of mood disorders, and for their treatment with cognitive behavioural psychotherapy.